Big book of ABC - Brooks,Felicity (London Usborne Publishing Ltd, 2018)
Sophia Touliatou's dynamic and joyous illustrations and some unusual word combinations make this an alphabet book like no other. Through busy, annotated pages children are introduced to upper and lower-case letters, pictures of things they are associated with (from amazing armadillos to zippy zebras) and facts about them. An unusual approach to an alphabet book and an eye-catching and quirky illustration style will make this title stand out in a crowded retail environment. An engaging and enjoyable way for children to learn letter recognition, letter sounds and alphabetical order.